PENEGAKAN HUKUM PIDANA TERHADAP PUNGUTAN LIAR BAGI PEDAGANG DI PASAR TRADISIONAL BAMBU KUNING KOTA BANDAR LAMPUNG - Bari Saputra; Zainudin Hasan; Dimas Fajar A; Muhammad Rayhan Avryandilla (Peneliti.net, 2023)
Community development is also followed by increased crime or criminality, as do illegal levies. The need for law enforcement against illegal levies that occurred in community life, because illegal levies occur in various sectors of community life including the trade sector which also includes trades that exist in traditional markets that can involve traders and civil servants. Criminalization of illegal levies is limited to the offenders, so that not all offenders can be charged and punished for illegal levies, because only civil servants or state officials can be given criminal charges against illegal levies. In this research will discuss the implementation of law enforcement on cases of illegal levies that occurred in Bambu Kuning Market conducted by the Head of Market which is a Civil Servants along with factors affecting the occurrence of illegal levies. The research method used is empirical juridical method, a study that examines the behavior of the community arising from interacting with the system of existing norms. So in this research of law to examine the behavior of society, especially merchants will their awareness of the act of illegal levies with primary data collection methods and secondary data through literature and field studies. The method of presenting the data qualitatively in a description of illegal levies and methods of data analysis using descriptive analysis method. The process of law enforcement against the head of Bambu Kuning Market through several parts which is a system that is investigation, investigation and prosecution as well as the judiciary. The system in Lampung State Prosecutor as the party receiving direct reports from the complainants, immediately take action by conducting an investigation in advance, after proven the existence of illegal charges after it conducted an investigation to determine the suspect after the investigation and investigation. This can certainly give effect to prevent further illegal levies by civil servants or state officials.